(untitled) (Research, Society and Development, 2021)
Specific gravity analysis (SG) is the main indirect method for measuring the quality of hens’ eggshells and is widely used in research and by the productive sector.However, there is not standardization in the number of days that are generally used to carry out this assessment. In addition, the ambiental temperature may change over the SG evaluation days and, if elevated, the egg may lose water and carbon dioxide and alter the density of the internal content, masking the results and interfering with the accuracy of the same. Therefore, the objective of this work was to verify the number of days necessary to evaluate the quality of eggs through SG. A completely randomized design was used, in a 3x7 factorial scheme (three days of SG evaluation, and seven saline solutions). The results obtained were submitted to analysis of variance and, when significant, to the Tukey test at 5%. No significant differences were observed (p> 0.05) for SG in the three days evaluated, but differences were observed (p <0.05) between the percentages of eggs that fluctuated in the seven saline solutions and, According to the regression equation obtained, as the GE values increased, the amount of semi-heavy laying eggs that fluctuated in these densities also increased. Therefore, it can be concluded that just one day of GE evaluation is sufficient to safely and accurately determine the quality of the shell.